The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1103/physrevb.60.14049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alloying on the electron momentum density in the Cu-Ni system

Abstract: We report on the measurement of the three-dimensional electron momentum density ͑EMD͒ of a 22 nm Cu/22 nm Ni sandwich foil and of a Cu 0.50 Ni 0.50 alloy film with the same thickness, which was obtained from an identical sandwich by interdiffusion. The EMD's were measured by coincident detection of a Compton scattered photon with its recoil electron. The experiments were performed at the High-Energy beamline of the European Synchrotron Radiation Facility. The experimentally observed small change of the EMD due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…non-coincident Compton scattering experiments on Cu-Ni single crystals, absolute values of experimental CPs are difficult to interpret due to the presence of a background contribution of uncertain origin. The solid line in figure 12 represents KKR-CPA theory [46,53]. In view of the smallness of the effect, a reasonable agreement between theory and experiment is observed.…”
Section: Cu-ni Alloymentioning
confidence: 59%
See 1 more Smart Citation
“…non-coincident Compton scattering experiments on Cu-Ni single crystals, absolute values of experimental CPs are difficult to interpret due to the presence of a background contribution of uncertain origin. The solid line in figure 12 represents KKR-CPA theory [46,53]. In view of the smallness of the effect, a reasonable agreement between theory and experiment is observed.…”
Section: Cu-ni Alloymentioning
confidence: 59%
“…In this section we will report on the influence of alloying by comparing the EMD of Cu 0.50 Ni 0.50 with those of its pure constituents [46]. The electronic structure of this 3d transition-metal solid-solution alloy has received extensive attention.…”
Section: Cu-ni Alloymentioning
confidence: 99%
“…Neither data processing like a deconvolution procedure accompanied by frequency filtering nor background subtraction has been applied to our data. The solid line in Figure 8.5 represents KKR-CPA theory [20,22]. In view of the smallness of the effect a reasonable agreement between theory and experiment is observed.…”
Section: Cu-ni Alloymentioning
confidence: 60%
“…In this chapter we will report on the influence of alloying by comparing the EMD of Cu 0.50 Ni 0.50 with those of its pure constituents [20]. The electronic structure of this 3d transition-metal solid-solution alloy has received extensive attention.…”
Section: Cu-ni Alloymentioning
confidence: 99%
“…In the context of this work it is worth mentioning an interesting study of the Ni-Cu system by Metz et al [28], who observed directly the effects of alloying close to the Fermi energy, using the (γ , eγ ) coincidence technique. Their observations generally agree with the predictions of KKR-CPA theory; however, it is difficult to compare them directly with our results, mainly because of the very different composition of the alloys studied.…”
Section: Resultsmentioning
confidence: 99%